AB0832 IDENTIFICATION OF NATIVE AND CITRULLINATED AUTOANTIBODIES TO PSORIASIS RELATED-ANTIGEN PsoP27 IN SYNOVIAL FLUIDS OF PATIENTS WITH PSORIATIC ARTHRITIS. (13th June 2020) - Slobodkin, M.; Gertel, S.; Polachek, A.; Furer, V.; Elkayam, O.
Abstract : Background: Psoriatic arthritis (PsA) is an inflammatory joint disease. Unlike rheumatoid arthritis (RA), PsA is a "seronegative disease", with no diagnostic biomarkers, hence diagnosis is based on clinical evaluation alone. PsA is closely associated with psoriasis (PsO), with up to 1/3 of psoriatic patients developing PsA via unknown mechanism. PsoP27 is an antigen present in mast cells in psoriatic lesions and absent in skin uninvolved by psoriasis or in healthy controls (1), thus playing a significant role in inflammatory reaction in the psoriatic skin lesion (2). Its levels in skin lesions correlate with psoriasis activity (3). Though speculated to be involved in other inflammatory processes, this antigen has not been investigated in relation to PsA. Objectives: Our aim was to identify and determine the level of native and citrullinated PsoP27 antibodies (Ab) in serum and synovial fluid of patients with PsA compared to RA and osteoarthritis (OA), exploring a potential common inflammatory pathway in PsA and PsO. Methods: Synovial fluid (SF) and serum of PsA (n=35, m:f 24:11, median age 48, PsA median duration 8Y, PsO median duration 15Y) and RA (n=11, m:f 2:9, median age 60, median RA duration 13.5Y) patients were analyzed for the level of native and citrullinated PsoP27 Ab. SF derived from OA (n=13, m:f 1:12, median age 77) patients and sera of healthy donors (n=31) were used as controls. Samples were analyzed by ELISA. Results: SF levels of native and citrullinated PsoP27 Ab were significantly higher in PsA and RA compared to OA patients (Table 1 ). Significant correlation was observed between the SF levels of both forms of PsoP27 Ab and the swollen joints count (Native: p=0.029, r=0.39, Cit: p=0.041, r=0.369 ), psoriasis area and severity index (PASI) score (Native: p=0.011, r=0.56, Cit: p=0.008, r=0.369 ), and CRP levels (Native: p=0.017, r=0.446, Cit: p=0.03, r=0.408 ). In contrast, in RA patients there was no correlation between SF levels of PsoP27 Ab and the swollen joint count or CRP levels. Both forms of PsoP27 Ab were detected in sera of all study groups, at a similar level (Table 2 ). Conclusion: We determined for the first time the presence of antibodies to psoriatic-related autoantigen PsoP27, in SF of PsA, RA and OA patients. Low SF level of PsoP27 Ab in OA compared to a high Ab level in RA and PsA may suggest a potential new biomarker discriminating between inflammatory arthritis versus OA. Furthermore, we showed a positive correlation between the SF levels of antibodies to PsoP27 in SF and disease activity in PsA, but not in RA. Also, we demonstrated the presence of citrullination and antibodies against citrullinated peptides in PsA, a process thought to be specific to RA. Our results suggest that antibodies to PsoP27 in SF may be a potential biomarker in PsA, both for diagnosis and disease assessment. References: [1]Iversen OJ, Lysvand H, Jacobsen T, Bergh K, Lie BA. Arch Dermatol Res. 1995;287(5):503-5 [2]Iversen OJ, Lysvand H, Slupphaug G. Clin Immunol. 2017;174:10-7. [3]Dalaker M, Jacobsen T, Lysvand H, Iversen OJ. Acta Derm Venereol. 1999;79(4):281-4. Disclosure of Interests: None declared